(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article analyzes the legislation of the Republic of Uzbekistan regulating the issuance of court orders, with the aim of comparing it with similar norms in Russia, Germany and the USA. The grounds for issuing a court order, requirements for the form of the application, the procedure for consideration and grounds for refusal are considered. Particular attention is paid to the possibilities of borrowing foreign experience to improve the effectiveness of law enforcement practice in Uzbekistan.